2020
DOI: 10.24251/hicss.2020.155
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gamification in Health Behavior Change: A Review of Theory-driven Studies

Abstract: Gamification is increasingly being recognized as a tool to support a change in individuals' health behaviors. However, how and under which circumstances gamification is able to support health behavior change is still largely unexplored. This study follows the call for more theory-driven research on gamification by investigating the role of gamification in health behavior change theories (HBCTs). In order to do so, we conducted a systematic review of extant literature and identified 25 studies that explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 43 publications
3
32
0
2
Order By: Relevance
“…Considerable research has been undertaken by researchers and program developers to facilitate optimum adherence to digital health initiatives. Methods used to promote participant adherence include the adoption of a robust set of persuasive system design principles [ 2 , 4 , 5 ], provision of rewards and incentives, positive feedback [ 6 ], implementation of gamification techniques [ 7 , 8 ], and various forms of human support [ 9 ]. However, adherence to digital interventions remains to be problematic [ 3 ], and there is a paucity of research elucidating participant perspectives on the factors that impact adherence [ 10 ] in community-based, nonclinical groups.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has been undertaken by researchers and program developers to facilitate optimum adherence to digital health initiatives. Methods used to promote participant adherence include the adoption of a robust set of persuasive system design principles [ 2 , 4 , 5 ], provision of rewards and incentives, positive feedback [ 6 ], implementation of gamification techniques [ 7 , 8 ], and various forms of human support [ 9 ]. However, adherence to digital interventions remains to be problematic [ 3 ], and there is a paucity of research elucidating participant perspectives on the factors that impact adherence [ 10 ] in community-based, nonclinical groups.…”
Section: Introductionmentioning
confidence: 99%
“…It was also interesting to see that many experts approach gamification from a self-determination theory (SDT) perspective, which is by far the most prominent theoretical lens on gamification [25]. While we acknowledge the value of approaching gamification from an SDT perspective, we think that future research should also consider other theoretical perspectives that are more closely related to the context that gamification is applied in (e.g., theories unique to the health context for HBCSSs [26]).…”
Section: Discussionmentioning
confidence: 94%
“…For example, Earle et al (2018) describe an adaptation of personalized normative feedback for problematic alcohol use, while Vella et al (2018) describe a gamified wellbeing app that adapts techniques from acceptance and commitment therapy and positive psychology. However, previous research has identified a lack of application of health behavior change theory in gamified health and wellbeing technologies ( Lister et al, 2014 ; Schmidt-Kraepelin et al, 2020 ). Furthermore, applications of gamification for health and wellbeing also appear to lack adequate reference to motivational theory ( Johnson et al, 2016 ).…”
Section: Developing and Evaluating Gamified Technologies For Mental Hmentioning
confidence: 99%
“…Then, in the next section, “Interrogating Gamification for Mental Health and Wellbeing,” it examined the complexities of the game form to demonstrate that gamification is not just implementing surface-level game mechanics such as points, badges, or leaderboards. In the following section, “Developing and Evaluating Gamified Technologies for Mental Health and Wellbeing,” this article further explored the process of designing, developing, and clinically evaluating gamified technologies for mental health and wellbeing, through the application of theory, methodologies, processes, and frameworks which are standard in their fields of origin, but rarely combined (as identified by, e.g., Schmidt-Kraepelin et al, 2020 ).…”
Section: Recommendations For Implementing Gamification For Mental Heamentioning
confidence: 99%
See 1 more Smart Citation